1998
DOI: 10.1097/00007890-199812150-00023
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Colitis Mimicking a Colonic Neoplasm or Ischemic Colitis 4 Years After Heart Transplantation

Abstract: CMV colitis should be suspected in any heart transplant patient with signs or symptoms of abdominal pathology, even without classical signs or symptoms of CMV infection. If stenotic lesions are present, surgery may be required not only to remove the obstruction but also to rule out malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Because invasive biopsy is necessary to demonstrate the typical "owl eye" intranuclear inclusion bodies of CMV, diagnosis is often delayed. Reports of CMV colitis in patients who test positive for human immunodeficiency virus have noted the cecum to be the most frequent site of involvement, but a review of CMV colitis in immunocompetent patients noted the sigmoid colon to be most frequently involved [1][2][3][4][11][12][13][14][15][16][17][18] (Table I). In conclusion, this illustrative case presents an immunocompetent patient who presented with signs and symptoms of a nonspecific colitis of uncertain cause, emphasizing the difficulty of distinguishing, both clinically and radiologically, infectious from noninfectious cause.…”
Section: Colitis Mimicking Ischemic Colitismentioning
confidence: 99%
“…Because invasive biopsy is necessary to demonstrate the typical "owl eye" intranuclear inclusion bodies of CMV, diagnosis is often delayed. Reports of CMV colitis in patients who test positive for human immunodeficiency virus have noted the cecum to be the most frequent site of involvement, but a review of CMV colitis in immunocompetent patients noted the sigmoid colon to be most frequently involved [1][2][3][4][11][12][13][14][15][16][17][18] (Table I). In conclusion, this illustrative case presents an immunocompetent patient who presented with signs and symptoms of a nonspecific colitis of uncertain cause, emphasizing the difficulty of distinguishing, both clinically and radiologically, infectious from noninfectious cause.…”
Section: Colitis Mimicking Ischemic Colitismentioning
confidence: 99%
“…The most commonly affected sites included the esophagus [9], the stomach [6,[9][10][11], and the large intestine [6]. Pseudotumoral appearance of HCMV infection has been described mainly in patients who have AIDS [6][7][8][9][10][11] or who have received an organ transplant [7,12,13], although occasional cases were detected in patients with common variable immunodeficiency syndrome [14] or chronic renal failure [15].…”
Section: Two Cases Of Human Cytomegalovirus (Hcmv) Colitis With Pseudmentioning
confidence: 99%
“…Progressive bowel obstruction and vomiting have also been reported [10]. Radiological studies (barium enema radiography or CT scanning) have shown a concentric or eccentric stenotic area, 5-8 cm long, accompanied by irregular mucosal thickening and rigidity of the wall [12][13][14][15]. The presence of single or multiple ulcerations is common.…”
Section: Two Cases Of Human Cytomegalovirus (Hcmv) Colitis With Pseudmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopy fi ndings typically show colitis, ulcers and very rarely pseudopolyps, pseudomembranes [7], and even mass lesions [13,14]. Ulcers are typically well defi ned and punched out in appearance [15], but may enlarge and coalesce in the later stage of CMV colitis, producing diffuse redness, erosions, bleeding, and sloughing mucosa throughout the colon [16].…”
Section: Endoscopic Findings Of CMV Colitismentioning
confidence: 99%